The emerging role of ACE2 in physiology and disease - Hamming, I (John Wiley & Sons, Ltd., 2007)

(untitled) (J Pathol)
The renin–angiotensin–aldosterone system (RAAS) is a key regulator of systemic blood pressure and renal function and a key player in renal and cardiovascular disease. However, its (patho)physiological roles and its architecture are more complex than initially anticipated. Novel RAAS components that may add to our understanding have been discovered in recent years. In particular, the human homologue of ACE (ACE2) has added a higher level of complexity to the RAAS. In a short period of time, ACE2 has been cloned, purified, knocked‐out, knocked‐in; inhibitors have been developed; its 3D structure determined; and new functions have been identified. ACE2 is now implicated in cardiovascular and renal (patho)physiology, diabetes, pregnancy, lung disease and, remarkably, ACE2 serves as a receptor for SARS and NL63 coronaviruses. This review covers available information on the genetic, structural and functional properties of ACE2. Its role in a variety of (patho)physiological conditions and therapeutic options of modulation are discussed. Copyright © 2007 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.